Problems of closure of spatial lever mechanisms with variable contours - Kanlybaev Оразалы; Satkalieva Марфуга; Galimov Ержан (Рroblems of engineering and professional education, 2023)
An analytical method for determining the parameters of the spatial grip mechanism is proposed for use in the design of space manipulation devices. The solutions of the synthesis calculation and its numerical results are presented.